2018
DOI: 10.1111/desc.12743
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal relation between sleep and memory in infancy: Memory‐dependent adjustment of sleep spindles and spindle‐dependent improvement of memories

Abstract: Sleep spindle activity in infants supports their formation of generalized memories during sleep, indicating that specific sleep processes affect the consolidation of memories early in life. Characteristics of sleep spindles depend on the infant's developmental state and are known to be associated with trait-like factors such as intelligence. It is, however, largely unknown which state-like factors affect sleep spindles in infancy. By varying infants' wake experience in a within-subject design, here we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 51 publications
(100 reference statements)
4
40
0
Order By: Relevance
“…These findings resonate with a recent infant study, in which state‐dependent changes in spindle density predicted generalization of novel object labels 1 day after learning (Friedrich, Mölle, Friederici, & Born, ). Furthermore, a developmental MEG study in children aged 8–12 years found that activity in inferior frontal gyri and medial prefrontal cortex was associated with recall of novel object associations (i.e., semantic learning) following sleep but not wake; whereas the wake group showed significantly greater hippocampal activation (Urbain et al, ).…”
Section: Introductionsupporting
confidence: 89%
“…These findings resonate with a recent infant study, in which state‐dependent changes in spindle density predicted generalization of novel object labels 1 day after learning (Friedrich, Mölle, Friederici, & Born, ). Furthermore, a developmental MEG study in children aged 8–12 years found that activity in inferior frontal gyri and medial prefrontal cortex was associated with recall of novel object associations (i.e., semantic learning) following sleep but not wake; whereas the wake group showed significantly greater hippocampal activation (Urbain et al, ).…”
Section: Introductionsupporting
confidence: 89%
“…Finally, the correlation of spindle activity over central-parietal brain regions with the N400 effect for words paired with new objects, which had been observed in recent infant studies [28][29][30] , failed to meet statistical significance after correcting for multiple testing (highest correlation with spindle RMS at P4: r = −0.437, P = 0.016, adjusted α = 0.008; overall correlation with mean spindle RMS amplitude over the left and right central and parietal regions: r = −0.174, P = 0.358). This weak relation suggests that infants did not build substantial new semantic memories during their nap.…”
Section: Resultsmentioning
confidence: 65%
“…NonREM sleep with a substantial amount of central-parietal fast sleep spindles in the 13-15 Hz frequency range supports semantic generalization of memories even in infants [28][29][30] . The amount of central-parietal fast spindle activity, in turn, is affected by an infant's processing of novel experience immediately before a nap.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Encoding, subsequent sleep, and consolidation are intertwined tightly. In a study of 14‐ to 16‐month‐olds (Friedrich, Mölle, Friederici, & Born, ), hearing unknown labels for exemplars of unknown categories produced more sleep spindle activity during a subsequent nap than hearing known labels for exemplars of known categories. In turn, sleep spindle activity was related to memory performance assessed 24 hr later.…”
Section: Sleep‐dependent Memory In Infants: Looking Aheadmentioning
confidence: 99%